Remote assessment of ADHD in children and adolescents: recommendations from the European ADHD Guidelines Group following the clinical experience during the COVID-19 pandemic: review - Pothula, Santosh; Cortese, S.; Hollis, C.; Bölte, S.; Daley, D.; Coghill, D.; Holtmann, M.; Sonuga-Barke, E. J. S.; Buitelaar, J.; Banaschewski, Tobias; Stringaris, A.; Döpfner, M.; et al. (European child & adolescent psychiatry, 2023)
The COVID-19 pandemic led ADHD services to modify the clinical practice to reduce in-person contact as much as possible to minimise viral spread. This had far-reaching effects on day-to-day clinical practice as remote assessments were widely adopted. Despite the attenuation of the acute threat from COVID, many clinical services are retaining some remote practices. The lack of clear evidence-based guidance about the most appropriate way to conduct remote assessments meant that these changes were typically implemented in a localised, ad hoc, and un-coordinated way. Here, the European ADHD Guidelines Group (EAGG) discusses the strengths and weaknesses of remote assessment methods of children and adolescents with ADHD in a narrative review based on available data and expert opinions to highlight key recommendations for future studies and clinical practice. We conclude that going forward, despite remote working in clinical services functioning adequately during the pandemic, all required components of ADHD assessment should still be completed following national/international guidelines; however, the process may need adaptation. Social restrictions, including changes in education provision, can either mask or exacerbate features associated with ADHD and therefore assessment should carefully chart symptom profile and impairment prior to, as well as during an ongoing pandemic. While remote assessments are valuable in allowing clinical services to continue despite restrictions and may have benefits for routine care in the post-pandemic world, particular attention must be paid to those who may be at high risk but not be able to use/access remote technologies and prioritize these groups for conventional face-to-face assessments.
Online veröffentlicht: 11. Februar 2023
Gesehen am 23.07.2024